2022
DOI: 10.3389/fnut.2022.920791
|View full text |Cite
|
Sign up to set email alerts
|

Linear and non-linear Mendelian randomization analyses of sex-specific associations between sleep duration and hyperuricemia

Abstract: BackgroundObservational studies have suggested a potential non-linear association between sleep duration and hyperuricemia. However, the causal nature and sex-specific differences are poorly understood. We aimed to determine the shape of sex-specific causal associations between sleep duration and hyperuricemia in the UK Biobank.MethodsLogistic regression was used to investigate the observational association between self-reported sleep duration and hyperuricemia among 387,980 white British participants (mean ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 60 publications
0
2
0
Order By: Relevance
“…For example, Zou et al found that short sleep is genetically associated with an increased risk of HUA among the white British population. 22 A study among Chinese government employees found that short nocturnal sleep duration was associated with a higher risk of HUA. 20 The mechanisms of the short sleep duration and HUA is still unclear.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Zou et al found that short sleep is genetically associated with an increased risk of HUA among the white British population. 22 A study among Chinese government employees found that short nocturnal sleep duration was associated with a higher risk of HUA. 20 The mechanisms of the short sleep duration and HUA is still unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Thirdly, different types of diseases also affect SUA. Relevant evidence pointed out that SUA, a major antioxidant agent, might play a key role in oxidative stress [52]. Previous articles have shown that oxidative stress might be of importance in the pathophysiology of bipolar disorder, schizophrenia, and major depressive disorder [53][54][55].…”
Section: Discussionmentioning
confidence: 99%